2014
DOI: 10.3390/v6030968
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Homology-Directed Repair in T98G Glioblastoma Cells Due to Interactions between Wildtype p53, Rad51 and HCMV IE1-72

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous pathogen capable of causing life threatening consequences in neonates and immune-compromised individuals. HCMV inflicts site-specific double strand breaks (DSBs) in the cellular genome. DNA damage infliction raises the corollary question of virus modulation of DNA repair. We recently reported HDR was stimulated in wt human foreskin fibroblasts (HFFs) during fully permissive infection or expression of the HCMV protein IE1-72 (IE72). These studies have been extended i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…It was previously demonstrated that SPOC1 modulates DNA repair kinetics and is recruited to DNA doublestrand breaks in an ATM-dependent manner (24). Since there is increasing evidence that the IE1 protein is able to modulate the DNA damage response during HCMV infection, we assumed that IE1 might be involved in the upregulation of SPOC1 (27)(28)(29)(30). In order to investigate this, we utilized IE1-inducible HFF cells (HFF-IE1 Tet-On) and analyzed SPOC1 expression levels in the presence or absence of IE1 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It was previously demonstrated that SPOC1 modulates DNA repair kinetics and is recruited to DNA doublestrand breaks in an ATM-dependent manner (24). Since there is increasing evidence that the IE1 protein is able to modulate the DNA damage response during HCMV infection, we assumed that IE1 might be involved in the upregulation of SPOC1 (27)(28)(29)(30). In order to investigate this, we utilized IE1-inducible HFF cells (HFF-IE1 Tet-On) and analyzed SPOC1 expression levels in the presence or absence of IE1 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Further research found that the IE1 protein, in a novel way, can activate flap endonuclease 1 (FEN1), a cellular factor recently identified to be involved in HR-mediated repair of stalled replication forks by actively inducing DSBs [ 171 ], hence restarting stalled replication forks in viral replication [ 172 ]. Furthermore, IE1 binds to p53 and inhibits p53’s inhibitory impact on Rad51, enabling HR [ 173 ]. Rad51 is a key regulator of HR, and its levels are much higher in HCMV-infected human foreskin fibroblasts (HFFs) [ 21 ], but not in normal cells [ 174 ].…”
Section: Hcmv Infection Affects Damage Repair Mechanisms During Ddrmentioning
confidence: 99%
“…89 The viral culture in HFFs has also been well documented, especially for the isolation and identification of mechanisms of the pathogenesis of cytomegalovirus in the cells. [90][91][92][93][94] HFFs have also been used to culture and study the varicella-zoster virus; 95,96 in the presence of a virus that has been implicated in the cytotoxic effects caused by enterovirus 97,98 by Coxsackie B virus type 1, 99,100 and evaluation of the mechanisms of infection and pathogenesis of herpes simplex virus type 1. 18,101 Human herpes virus 8 is associated with Kaposi's sarcoma 102 and Japanese encephalitis virus.…”
Section: Culture Of Hffs For the Diagnosis Of Pathogenic Microorganismsmentioning
confidence: 99%